(untitled) (Dhaka University Law Journal, 2025)
This article critically examines the international legal debate over fixed versus ambulatory maritime baselines under the UN Convention on the Law of the Sea, driven by rising sea levels. It analyses the legal justifications, state practice, and equity considerations for vulnerable states. Fixed baselines promise stability and equity for vulnerable states but challenge traditional interpretations. Ambulatory baselines align with traditional principles but severely disadvantage states impacted by sea-level rise. This article provides a synthesised, critical overview of this urgent debate, juxtaposing legal principles with climate adaptation needs and highlighting the existing tensions and lack of a clear resolution. Its primary contribution is to propose a pragmatic path forward that moves beyond this binary deadlock, arguing for securing the outer limits of maritime zones through collective, equity-based interpretation, thereby offering a novel solution in response to the intractable challenges of fixing the baseline itself. Dhaka University Law Journal, 2025, 36 (1), 65-83